2022
DOI: 10.1021/acs.est.1c06686
|View full text |Cite
|
Sign up to set email alerts
|

Dehalococcoides-Containing Enrichment Cultures Transform Two Chlorinated Organophosphate Esters

Abstract: Although chlorinated organophosphate esters (Cl-OPEs) have been reported to be ubiquitously distributed in various anoxic environments, little information is available on their fate under anoxic conditions. In this study, we report two Dehalococcoides-containing enrichment cultures that transformed 3.88 ± 0.22 μmol tris(2-chloroethyl) phosphate (TCEP) and 2.61 ± 0.02 μmol tris(1-chloro-2-propyl) phosphate (TCPP) within 10 days. Based on the identification of the transformed products and deuteration experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This was also supported by the evidence that the concentrations of DNBP, BEHP, DEP, BBOEP, and DOTP in proglacial sediments (15–112 pg/g dw, Table S6) were higher than those in ocean sediments (ND-95 pg/g dw). In addition to photodegradation, microbial degradation of tri-OPEs might be another important source of di-OPEs in sediments. , The half-lives of TPhP, TCIPP, TNBP, and TOTP in sediments ranged from 78 to 542 days (Table S1) and were much longer than their photodegradation half-lives (0.14–20 d). This indicated that the efficiency of microbial degradation of tri-OPEs in sediments might be lower than the efficiency of photodegradation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was also supported by the evidence that the concentrations of DNBP, BEHP, DEP, BBOEP, and DOTP in proglacial sediments (15–112 pg/g dw, Table S6) were higher than those in ocean sediments (ND-95 pg/g dw). In addition to photodegradation, microbial degradation of tri-OPEs might be another important source of di-OPEs in sediments. , The half-lives of TPhP, TCIPP, TNBP, and TOTP in sediments ranged from 78 to 542 days (Table S1) and were much longer than their photodegradation half-lives (0.14–20 d). This indicated that the efficiency of microbial degradation of tri-OPEs in sediments might be lower than the efficiency of photodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to photodegradation, microbial degradation of tri-OPEs might be another important source of di-OPEs in sediments. 15,16 The half-lives of TPhP, TCIPP, TNBP, and TOTP in sediments ranged from 78 to 542 days (Table S1) and were much longer than their photodegradation half-lives (0.14−20 d). This indicated that the efficiency of microbial degradation of tri-OPEs in sediments might be lower than the efficiency of photodegradation.…”
Section: Source Identification Of Opesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main products of ultrasonic treatment TCEP were monoester and diester. Zhu et al [ 44 ] reported two enriched cultures containing dehalococcoides that transformed TCPP and TCEP within 10 days. The results deduced that TCEP might be converted to di (2-chloroethyl) phosphate and ethylene based on the identification of the conversion products and deuteration experiments by radical mechanism followed by C–O bond cleavage.…”
Section: Degradation Mechanism and Productsmentioning
confidence: 99%